The influence of language use of Turkish /English bilingual speakers on their personal and behavioural attitudes - Mehmet Tunaz; Emrah Muyan (Ömer Gökhan Ulum, 2021)
This study investigated if Turkish instructors of English, who have learned English as a foreign language following the acquisition of basic mother language, by utilizing a similar research procedure as in Hamers and Blanc (2004). It was aimed to reveal whether consecutive bilinguals of Turkish/English speakers feel like different people depending on their language preferences. Four female and four male Turkish instructors of English were involved as the participants of the study. The participants were selected randomly and interviewed personally. They all learned English as a foreign language at school. The data were collected through a semi-structured interview which had three parts. The first part of the interview elicited background knowledge about the participants. Secondly, an open ended question "Do you feel like a different person when you speak English and Turkish?" was asked to get insight into their behavioural attitudes in different contexts. Thirdly, they were asked to complete the same sentence "Eğer eşimle sorun yaşarsam..../ If I had an argument with my wife or husband...." both in English and Turkish, and react to a given situation "If someone passed in front of you in a queue without permission, how would you react?" in English and Turkish to investigate whether they prefer to be more polite in one of the languages. The data were analyzed qualitatively through a phenomenological research approach. The results revealed that Turkish instructors of English, who are consecutive bilinguals, feel like different people when they speak English and Turkish depending on the situation. As the sources of their perceptions, participants emphasized two main factors: (1) the context they learned English and (2) the context they use English.